Bibliometric Analysis of Dividend Policy and Firm Value - Judijanto, Loso (Eastasouth Institute, 2025)
This study conducts a comprehensive bibliometric analysis to map the intellectual landscape, research evolution, and thematic trends in the domain of dividend policy and firm value. Utilizing data from the Scopus database spanning 2000 to 2024, the analysis includes performance metrics, co-authorship networks, institutional collaborations, and keyword co-occurrence mapping, visualized through VOSviewer. The results highlight dividend policy, firm value, corporate governance, and capital structure as the most frequently studied and interconnected themes. A temporal overlay analysis reveals a recent shift toward emerging topics such as sustainability, corporate social responsibility, and information asymmetry, indicating a broader integration of ESG and stakeholder theory into dividend research. The study offers practical insights for financial managers and investors, emphasizes theoretical intersections between finance and governance, and outlines gaps for future scholarly exploration. Despite limitations related to database scope and keyword sensitivity, the findings serve as a valuable foundation for both academic inquiry and policy-oriented decision-making in corporate finance.